Remifentanil in der Kardiochirurgie : Hämodynamik, Aufwachverhalten und endogene Stressreaktion herzchirurgischer Patienten unter Remifentanil-, Sufentanil-, Alfentanil- und Fentanylnarkose - Pack, Anette; Justus Liebig University Giessen (My University, 2007)
Zum prospektiv-randomisierten Vergleich endogener Stressparameter sowie des Kreislauf- und Aufwachverhaltens nach aortokoronaren Bypassoperationen wurden vier Gruppen mit je 12 Patienten während und nach total intravenöser Anästhsie mit Remifentanil bzw. Fentanyl, Alfentanil oder Sufentanil untersucht. Alle Patienten erhielten zusätzlich Propofol als Hypnotikum. Es fanden sich signifikant höhere Plasma-Adrenalinspiegel in der Fentanygruppe zu zwei Messzeitpunkten, besonders zum Ende der Aortenabklemmzeit korrelierte dies mit einem signifikant erhöhten ADH-Plasma-Spiegel. Auch zu den übrigen intraoperativen Messzeitpunkten waren die Adrenalinspiegel in der Fentanylgruppe tendenziell am höchsten. Für die Patienten des Remifentanilkollektivs ließen sich zu keinem Messzeitpunkt signifikant erhöhte Stresshormonspiegelnachweisen. Bezüglich der Hämodynamik ergaben sich für den arteriellen Mitteldruck die konstantesten Werte in der Alfentanilgruppe, an drei Messzeitpunkten fanden sich signifikante Unterschiede zu anderen Gruppen. Die Patienten der Remifentanilgrupppe wachten siginifikant schneller auf als Fentanyl- und Alfentanilpatienten und waren siginifikan früher extubiert als die Patienten aller anderen Gruppen. Ein EInfluss auf die postoperativeIntensiv- und Gesamtliegezeit im Krankenhaus ergab sich daraus nicht. Damit auf Dauer durch die frühzeitige Extubation der Patienten unter Remifentanil auch die postoperativen stationören Verweilzeiten reduziert werden und damit Kosten gesenkt werden können, bedarf es noch organisatorische und strukturelle Veränderungen, insbondere auf den der Intensivstation nachgeordneten Überwachungseinrichtungen für frisch operierte Patienten.

The present thesis is a prospective comparison of endocrine stress parameters, circulation and arousal behaviour of patients during and after aorto-coronary bypass surgery. The Patients were randomly fitted into 4 groupsof different opioidtreatments: remifentanil, fentanyl, alfentanil or sufentanil supplemented with propofol. Into each group were included 12 patients. In patients treated with fenanyl I measured significantly elevated plasma-adrenalin-concentrations at 2 different time points during surgery. These enhanced plasma-concentrations correlated strongly with increased ADH-plasma-concentrations towards the endof the aortal ligation. In patients, belonging to the fentanyl treated group, the plasma-adrenalin-concentrations showed the tendency to be highest at all other time points chosen for measurements during surgery. In patients fitted into the remifentanil treatment group, I measured no increased plasma-concentrations of stress hormones, at any chosen time point during the present study. In terms of circulation and hemodynamic parameters during the pharmacological treatments I observed the most constant mean arterial pressures in patients who received alfentanil. Furthermore these values were significantly different compared to all other treatment groupsat three different time points during the surgical procedure. Focusing on the arousal behaviour, I measured a significant faster awakening of patients receiving remifentanil, compared to patients who underwent surgery when fentanyl or alfentanil was applied. Patients receiving remifentanil could be siginificantly earlier extubated than patients from all other treatment groups. This early extubation of remifentanil treated patients did not result in shorterperiodsthepatients had to stay on the intensive care unit, or in the total period the patients stayed in hospital.To reduce really the period in patients stay on the intensive care unit after early extubation and previous remifentanil treatment one has to focus on certain points. Organisational and structural changes, on the wards and monitoring units have to be made to be able to care for patients immediatly after aorto-coronary bypass surgery.
Remifentanil in cardiac surgery : circulation, arousal behaviour and endocrine stress parameters in patients treated with remifentanil, sufentanil, alfentanil or fentanyl while undergoing aorto-coronary bypass surgery
Keywords: ddc:610